2015
DOI: 10.3390/fib3040560
|View full text |Cite
|
Sign up to set email alerts
|

Properties of PAN Fibers Solution Spun into a Chilled Coagulation Bath at High Solvent Compositions

Abstract: Abstract:In this work, multifilament, continuous polyacrylonitrile (PAN) fiber tow was solution spun mimicking industrial processing at the small pilot scale (0.5 k tow), while carefully altering the composition of the coagulation bath, in order to determine the effect on the resulting fiber shape, density, orientation, and tensile properties at varying points in the spinning process. Novel here are the abnormally high coagulation bath solvent compositions investigated, which surpass those often reported in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…[21,53] However, by applying higher draw ratio and stretching, the crystallinity index can be increased, as due to the drawing and stretching mechanism, the molecules inside the polymeric matrix are arranged properly rather than a random orientation. [54,55] For example, in our previous study, the crystallinity index of the control PAN_M1 fibers was around 55%. [26] Nevertheless, owing to the doubled draw ratio, the crystallinity index of the control PAN_M2 fibers increased by around 45% in the current study.…”
Section: Xrd Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…[21,53] However, by applying higher draw ratio and stretching, the crystallinity index can be increased, as due to the drawing and stretching mechanism, the molecules inside the polymeric matrix are arranged properly rather than a random orientation. [54,55] For example, in our previous study, the crystallinity index of the control PAN_M1 fibers was around 55%. [26] Nevertheless, owing to the doubled draw ratio, the crystallinity index of the control PAN_M2 fibers increased by around 45% in the current study.…”
Section: Xrd Analysismentioning
confidence: 86%
“…[56] In similar, the internal molecular alignment and the direction of the fibrils may be rearranged with the implementation of the higher proportion of drawing and stretching to the fibers. [52,55] Due to the drawing and stretching, the reduction in the fiber diameter was evident with the elimination of the voids areas, which is also known as cavity healing of the fibers. [52] Furthermore, the crystallinity of the fibers increased and assisted to achieve the higher mechanical properties of the fibers compared to the previous fibers.…”
Section: Effect Of Stretchingmentioning
confidence: 99%
“…48 In a diffraction pattern, the halopeaks are due to the higher crystalline region whereas the broader peaks represent the lower crystalline or higher amorphous region. 40 From Table III, it can be found that the control PAN fibers showed around 55% crystallinity whereas it was gradually reduced with the increment of alpaca content in the composite fibers. As the broadness of the peak at 17 of the composite fibers increased (Figure 9), the crystallinity of the composite fibers decreased ( Table III).…”
Section: Crystallinity and Moisture Propertiesmentioning
confidence: 93%
“…In this study, five spinning velocities (v s ) of the dope (polymer solution) at the spinneret nozzle were considered with a jet-stretch ratio (v PAN /v s ) of five [7,24,25]. Table 1 indicates the PAN-bundle velocity (v), porosity (φ), and viscous resistance (1/K) according to the five cases.…”
Section: Mesh Structure and Materials Propertiesmentioning
confidence: 99%